The Sacred/Secular Divide and the Christian Worldview - Kim, David (Journal of business ethics, 2012)
Many employees with strong religious convictions find themselves living in two separate worlds: the sacred private world of family and church where they can express their faith freely and the secular public world where religious expression is strongly discouraged. We examine the origins of sacred/secular divide, and show how this division is an outcome of modernism replacing Christianity as the dominant worldview in western society. Next, we make the case that guiding assumptions (or faith) is inherent in every worldview, system of thought, or religion and also show that scientific reason can never be a comprehensive or totalizing meaning system, particularly in the realm of ethics. The underlying assumptions of the sacred/secular divide are seriously questioned which has implications for employees who desire to integrate faith and career. Finally, we offer possibilities for individuals and corporate entities to integrate the personal and sacred with the institutional and secular.